2022
DOI: 10.14406/acu.2022.012
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Rapid Prototyping Instructional Systems Design in Meridianology Laboratory

Abstract: Objectives : Instructional design is the systematic approach to the Analysis, Design, Development, Implementation, and Evaluation of learning materials and activities. We aimed to apply the rapid prototyping to instructional systems design (RPISD) in meridianology laboratory, a subject in which students train acupuncture to develop lesson plan. Methods : The needs of the stakeholders including client, subject matter expert and students were analyzed using the performance needs analysis model. Task analysis was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The RPISD model consists of analysis, design, and usability testing of early prototypes, development, implementation, and evaluation, with several overlapping phases [8]. We have reported this process of the early prototype [9] and materials development [10] in our previous studies. The present study summarizes the previously reported analysis, design, and development process and details the implementation and evaluation results of the program.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The RPISD model consists of analysis, design, and usability testing of early prototypes, development, implementation, and evaluation, with several overlapping phases [8]. We have reported this process of the early prototype [9] and materials development [10] in our previous studies. The present study summarizes the previously reported analysis, design, and development process and details the implementation and evaluation results of the program.…”
Section: Methodsmentioning
confidence: 99%
“…After class, usability testing was conducted by interviewing the client, students, and subject matter experts. Based on the usability testing, a second prototype was developed and presented [9]. Peer roleplay, George's Five Methods for Teaching Clinical Skills [12], and the Objective Structured Clinical Examination (OSCE) were included as instructional strategies.…”
Section: Design and Development Of The Programmentioning
confidence: 99%
“…Stakeholders in Systematic Instructional DesignThe instructional designer constructively reflected the opinions of the client, subject matter expert(SME), and user in the design process. (Modified this figure from the works of Cho E.B., Kim J.H., Hong J.S 16…”
mentioning
confidence: 99%